Ketuhanan dan Kerakyatan: Telaah Politik Islam KH Wahid Hasyim - Ferhadz Ammar Muhammad (Tebuireng: Journal of Islamic Studies and Society, 2024)
This paper discusses the Islamic political thought of KH Abdul Wahid Hasyim - more often written by KH Wahid Hasyim (1914-1953) in the context of statehood. This study shows that Wahid Hasyim can be categorized as a figure in the discourse of Islamic political thought from Indonesia. This research uses qualitative methods and literature approaches. The data obtained came from library materials written directly by Wahid Hasyim and reliable sources in the form of main books discussing Wahid Hasyim, anthologies of works from academics, and reviews from newspapers. The information obtained was analyzed using descriptive-analytical and historical methods. This research found that Wahid Hasyim's thoughts on statehood were formulated through two themes, namely divinity and democracy. In contrast to a number of Islamic political thinkers who tend to be biased towards one of the two, Wahid Hasyim is actually able to integrate divinity and democracy in one frame, namely Indonesian democracy, as can be seen in a number of his works.